Riba versus Sedekah - Trisno Wardy Putra (LPPM IAIN Sorong, 2019)
The focus of this discussion concerns the Usury Versus Alms. The purpose of this study is to provide an explanation of how the sharia views towards usury and alms and to find out how the effects of usury and alms. This research is in the form of a comparison between usury and alms in the view of the Qur'an and the Sunnah and through the opinions of the scholars and interpreters of usury and alms. The results of the discussion stated that usury is an activity that is forbidden in the Sharia and will not add to the side of Allah SWT. Furthermore alms is a religious activity that Allah SWT commands to Muslims and of course people who do alms will be receive multiple reward. The impact of usury will have a negative effect comparing to giving charity that gives a positive effect both in personal, economic and social aspects of the community.